Provinciale Prijs Beeldende Kunst 2003 : Geert Goris, Els Vanden Meersch, Vaast Colson. - Helsen, Ludo; Vuegen, Christine; Lauwaert, Dirk, 1944-2013; Meewis, Ben; Koningin Fabiolazaal, Antwerpen (Antwerpen : [s.n.], 2003)
Goris, Geert ; Vanden Meersch, Els ; Colson, Vaast
Schenking Geert Goris
Prijs van Provincie Antwerpen, Koningin Fabiolazaal, Antwerpen
kunstcatalogus